2021
DOI: 10.1186/s13023-020-01579-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in patients with hereditary hemorrhagic telangiectasia

Abstract: Background Retrospective questionnaire and healthcare administrative data suggest reduced life expectancy in untreated hereditary hemorrhagic telangiectasia (HHT). Prospective data suggests similar mortality, to the general population, in Denmark’s centre-treated HHT patients. However, clinical phenotypes vary widely in HHT, likely affecting mortality. We aimed to measure predictors of mortality among centre-treated HHT patients. HHT patients were recruited at 14 HHT centres of the Brain Vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
(52 reference statements)
1
5
0
1
Order By: Relevance
“…It has been previously demonstrated that HHT patients with GI bleeding experience significant morbidity, requiring more transfusions and more emergency room and hospital admissions than other HHT patients [ 30 ]. Additionally, we recently reported that chronic GI bleeding is associated with increased mortality in HHT patients [ 31 ], in keeping with our observed higher mRS scores associated with this HHT manifestation. Further, a report on acute ischemic stroke patients (not HHT) demonstrated that patients who developed GI bleeding had a higher rate of mortality and disability (mRS grade greater than or equal to 4) than those who did not [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…It has been previously demonstrated that HHT patients with GI bleeding experience significant morbidity, requiring more transfusions and more emergency room and hospital admissions than other HHT patients [ 30 ]. Additionally, we recently reported that chronic GI bleeding is associated with increased mortality in HHT patients [ 31 ], in keeping with our observed higher mRS scores associated with this HHT manifestation. Further, a report on acute ischemic stroke patients (not HHT) demonstrated that patients who developed GI bleeding had a higher rate of mortality and disability (mRS grade greater than or equal to 4) than those who did not [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Among HHT patients, 20 (48%) had BAVM, 30 (71%) had pulmonary arteriovenous malformation (PAVM), 9 (21%) had gastrointestinal (GI) bleeding, and 3 of 37 with information (8%) had symptomatic liver vascular malformations (LVM). HHT organ involvement was defined as previously described [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The liver is the most commonly affected organ (hepatic AVMs) ( 8 ); however, the treatment options are limited and unsatisfactory. Although the vast majority of liver VMs are asymptomatic and do not require treatment, symptomatic liver VMs must be treated aggressively since they increase mortality ( 9 ). Intravenous bevacizumab helps relieve symptoms and has been used as a bridge to orthotopic liver transplant (OLT) ( 10 ).…”
Section: Discussionmentioning
confidence: 99%